Optimization of cutting parameters and surface roughness on dry turning of low carbon steel - Hou, Lo Wei (2012)
Cutting fluid play a very important role in machining but it also brings a lot of detrimental effects such as health hazards and environmental pollutions when it handled improperly. In addition, the cutting fluids also increase the amount of machining cost since it had been issues lately of its cost frequently higher than the cost of cutting tools. With this issue, dry machining becomes one of the solutions to solve this problem. The objective of this project is to optimize the cutting parameters and surface roughness on dry machining. Material chosen to be perform in this study is low carbon steel AISI 1019. The experiment is carried out with a full factorial design of 3 cutting parameters with 3 levels each onto dry Lathe machining. The surface roughness of workpiece is measured by using perthometer and the result is analyzed statistical by using STATISTICA software version 7.1. The optimum cutting parameters and surface roughness can be investigated through the ANOVA prediction with a level of confident 95 percent. The result investigate can help the industries to solve the problem by applying the investigated values of parameters not only in reducing the machining cost but also present a more environmental friendly machining operation.